2021
DOI: 10.17645/up.v6i2.3953
|View full text |Cite
|
Sign up to set email alerts
|

Blue-Green Playscapes: Exploring Children’s Places in Stormwater Spaces in Augustenborg, Malmö

Abstract: The urbanisation of cities increases the demands on, and complexity of, urban land use. Urban densification is challenging urban green space. Cities have responded to this challenge by adopting a multiple-use strategy where different functions share space. Shrinking open space has to contain solutions for everyday functions such as bicycle parking, waste sorting, blue-green stormwater systems, and playscapes. Values and functions that can reinforce and amplify each other are therefore of interest to study.<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, as BGS become permanent components of urban open space, they also need to be socially embedded [9] and adapt to the ongoing and ever-changing daily life. To increase the societal benefits of BGS, it is important to understand how they can provide better support to everyday life [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, as BGS become permanent components of urban open space, they also need to be socially embedded [9] and adapt to the ongoing and ever-changing daily life. To increase the societal benefits of BGS, it is important to understand how they can provide better support to everyday life [10].…”
Section: Introductionmentioning
confidence: 99%
“…Various research directions have been identified on children's outdoor play involving environmental protection, psychology, medicine, health, and urban or rural construction after searching the literature in the database of Scopus and Web of Science (Bartie et al, 2016;Gundersen et al, 2016;Buck et al, 2019;Furneaux and Manaugh, 2019;Nordbø et al, 2020;Mottaghi et al, 2021). This study focuses on the physical environmental types and characteristics of children's outdoor play in residential neighbourhoods.…”
Section: Review Topic and Definitions Of Its Related Conceptsmentioning
confidence: 99%